I Don't Want a Cold! - Tony Ross (London, United Kingdom Andersen Press Ltd, 2008)
It's the day of the royal picnic! The Little Princess has been looking forward to it for ages. When she wakes up that morning with a nasty, snuffly cold, she is determined not to let it spoil her fun - even if it means bending the rules a little!
Keywords: Read Aloud Section R